Research progress on load characteristics and dynamic response of multicamerate defense structure subjected to contact underwater explosion - WU Ting'ao; ZHANG Nu; HOU Hailiang; WU Guomin; ZHOU Xintao (Zhongguo Jianchuan Yanjiu, 2018)
In order to explore research progress into damage to multicamerate defense structures caused by contact underwater explosion, the present situation of domestic and overseas research is summarized in the two aspects of load characteristics and structural dynamic response. The research status of three typical loads are summarized:shock load caused by contact underwater explosion, bubble load under complicated boundary and shock load caused by the high-speed penetration of a liquid tank. At the same time, the research status of three typical structural dynamic responses are summarized:side plate, liquid tank and sandwich structure. The research results of domestic and foreign scholars on related issues are summarized, existing blind spots in the research content identified and problems requiring solutions put forward. This paper provides references for the design and optimization of multicamerate defense structures.